The micro-practices of project organizing in the Chinese construction sector: a sensemaking perspective. Issue 9 (2nd September 2022) - Qin, Beibei; Green, Stuart D.
Abstract: The organization of construction in the People's Republic of China has over recent decades undergone radical restructuring. The announcement of Deng Xiaoping's Open Door strategy in 1978 marked the beginning of the transition towards the espoused socialist market economy and the progressive introduction of market mechanisms. Existing research tends to focus on the derivation of "critical success factors" rather than the lived realities of those directly involved. In contrast, the current paper adopts a sensemaking perspective that privileges the transient roles and identities of those involved in the micro-processes of project organizing. The empirical focus lies on the sensemaking narratives of middle managers within three state-owned construction enterprises in the Chongqing city region. The findings illustrate how market mechanisms such as bidding and tendering play out in complex ways involving hybrid arrangements between new and pre-existing ways of working. The terminology of project management is seen to have played a performative role in establishing the "project" as the essential unit around which the socialist market is organized. Middle managers are further found to maintain multiple identities in response to the experienced paradoxes of the socialist market economy. The research provides new insights into the micro-processes of project organizing in China with broader implications for transitional economies elsewhere.